Active structures and thermal state of the Piton de la Fournaise summit revealed by combined UAV magnetic and thermal infrared measurements - Gailler, Lydie; Labazuy, Philippe; Régis, Edouard; Peltier, Aline; Ferrazzini, Valérie (Volcanica, 2022)
In this study, we demonstrate the strong potential of combining Unmanned Aerial Vehicle (UAV)-based thermal infrared (IR) and magnetic measurements to image the thermal state of volcanic edifices, as well as the distribution of active volcano-tectonic features at depth. Since magnetization is strongly dependent on temperature and alteration, thermally active structures are also associated with a decrease in magnetization. Based on the analysis of recent combined magnetic and infrared acquisitions, we focus on the recent evolution of the summit activity at Piton de la Fournaise. The comparison clearly highlights zones of major thermal activity, alteration and high permeability, and potentially areas of low mechanical resistance. Those observations provide information on preferential pathways for future activity, and also provide constraints on fluid transfer, diffusion, and cooling processes occurring within the volcano subsurface. Through reiterations, such combined UAV measurements are therefore particularly relevant in monitoring volcanic hazards before, during and after eruptions.